1982
DOI: 10.3109/08820138209094132
|View full text |Cite
|
Sign up to set email alerts
|

Forssman Antibody Levels in Sera of Cancer Patients

Abstract: By means of SRBC lysis in agarose gel and Forssman (F) liposome lysis assay, serum levels of F antibodies were determined in various cancer patients. F antibody titers of the patient's sera were shown to be lower than that of normal controls. Following radical surgery, F antibody titers were elevated significantly in most of the patients with advanced gastric, colorectal and lung cancer. Similar tends of anti-A antibody titers were observed in group O and B patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…[7][8][9][10][11][12][13] We previously examined the presence/absence of activating missense mutations at codon 230 or 296 of the human GBGT1 gene in the Catalogue of Somatic Mutations in Cancer Database. However, no such mutations were found, although the database lists 60 mutations in the GBGT1 gene in various cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13] We previously examined the presence/absence of activating missense mutations at codon 230 or 296 of the human GBGT1 gene in the Catalogue of Somatic Mutations in Cancer Database. However, no such mutations were found, although the database lists 60 mutations in the GBGT1 gene in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition to occurring in A pae individuals, FORS1 expression has also been reported in cancer cells/tissues from non-A pae individuals. [7][8][9][10][11][12][13] However, the molecular mechanisms that induce heterophilic FORS1 expression remained to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Forssman antibodies, has been documented earlier [19,20] . In our study, the postoperative elevation of antibody levels was found to be related to the low-differentiated carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The spe cificity of the corresponding antigen was shown to be dependent on the GalNac-GalNac portion of glycolipid of F-positive erythrocyte membrane [61] or the same two terminal sugars of glycoprotein isolated from tissues of F-positive species [62]. F-antibody ti ters in normal human sera vary from one individual to another [63] and they tend to increase in patients with carcinomas of the gastrointestinal tract after ra dical surgery [64], Significantly F antigen has been demonstrated in and isolated from various carcino mas [65][66][67][68], The mechanism of expression of F anti gen in malignancies is now being investigated [68,69], Finally, our recent studies have shown that agglu tinins against Victoria strain of NDV-treated group O red blood cells found in IM and other pathologic sera as well as some of antibodies to the NDV preparation are directed to the antigen of the hemagglutinin-neu raminidase subunit of the NDV [38][39][40], Interestingly, the antigen of the hemagglutinin-neuraminidase molecule recognized by these pathologic sera is also present in GPK tissues [38][39][40], Thus the NDV anti bodies were now classified into the GPK-positive group of human heterophile antibodies. …”
mentioning
confidence: 99%